2019
DOI: 10.1002/jmri.26985
|View full text |Cite
|
Sign up to set email alerts
|

Role of Breast MRI in the Evaluation and Detection of DCIS: Opportunities and Challenges

Abstract: Historically, breast magnetic resonance imaging (MRI) was not considered an effective modality in the evaluation of ductal carcinoma in situ (DCIS). Over the past decade this has changed, with studies demonstrating that MRI is the most sensitive imaging tool for detection of all grades of DCIS. It has been suggested that not only is breast MRI the most sensitive imaging tool for detection but it may also detect the most clinically relevant DCIS lesions. The role and outcomes of MRI in the preoperative setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 115 publications
5
14
0
Order By: Relevance
“…The specific features of DCIS are calcifications at digital mammography (70-90% of cases [36]) and non-mass enhancement at MRI contrast-enhanced sequences (up to 81% of cases [34,[37][38][39]); our results (86.7% of DCIS presented as non-mass enhancements, p < 0.001) are in substantial agreement with those data. A second MRI feature significantly associated with DCIS was T2 isointensity (78.6%, p < 0.001) (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The specific features of DCIS are calcifications at digital mammography (70-90% of cases [36]) and non-mass enhancement at MRI contrast-enhanced sequences (up to 81% of cases [34,[37][38][39]); our results (86.7% of DCIS presented as non-mass enhancements, p < 0.001) are in substantial agreement with those data. A second MRI feature significantly associated with DCIS was T2 isointensity (78.6%, p < 0.001) (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the patients included in this study (78.2%) were affected by invasive carcinoma NST, which is the most common type of BC, 12% by ILC, and about 10% by DCIS. Our distribution substantially reflected data reported in literature [31][32][33][34][35].…”
Section: Discussionsupporting
confidence: 88%
“…Only one lesion had a DCIS that was hormonal-positive and did not show any invasive component upon further examination of excised surgical specimen. Thus, a score of greater than 5, using a simple Kaiser score flowchart, could accurately predict DCIS in 97.6 % of cases, which is much easier than the complicated additional MR studies [34] suggested in the recent literature.…”
Section: Discussionmentioning
confidence: 93%
“…[5][6][7][8] Magnetic resonance imaging (MRI), the alternative to mammography is also radioactive, expensive, intensive, requires skilled technical assistance. 9 Furthermore, microcalcifications (MC) identification for BC screening on DCIS that is usually done via mammogram, MRI and ultrasound imaging may not be suitable for real-time clinical application and needs series of biopsies to confirm whether, the DCIS is benign or malignant, which again is a nerveracking protocol. 10 This reveals the unmet necessity to develop noninvasive, rapid, sensitive, reliable and non-radioactive method to diagnose DCIS.…”
Section: Dcis Stages Grades and Incidencementioning
confidence: 99%